The Role of Preoperative Computed Tomography in Nonsyndromic Craniosynostosis. Issue 2 (March 2019) - Alnaif, Nayif; Zhou, Mingsha; Galli, Rafael; Azzi, Alain J.; Alamri, Abdulrahman; Gilardino, Mirko
Abstract : Background: There is currently no consensus on the utility of preoperative computed tomography (CT) in nonsyndromic craniosynostosis. This systematic review and meta-analysis examines the evidence available on the necessity of preoperative CT for the treatment of nonsyndromic craniosynostosis. Methods: A comprehensive literature review of the National Library of Medicine (PubMed) database was performed. The following variables were analyzed: concordance of findings between clinical examinations and CT, incidental findings reported on imaging, and the effect of imaging on subsequent management. Concordance between clinical examination/CT and the presence of incidental findings were collected and displayed as descriptive data. The effect of imaging on subsequent diagnosis/management was analyzed by meta-analysis. Results: Eleven studies met the inclusion criteria for a total of 728 patients. Overall, physical examination concordance with CT diagnosis was 97.9% (371/379). Overall, incidental findings led to additional imaging/workup in 1.79% of cases (5/278). The results of the meta-analysis revealed that, in the absence of alternative imaging modalities, CT scans significantly altered diagnosis or led to additional investigations in 12 cases (4.8%, 95% confidence interval = 3%–8%). Preoperative CT scans led to additional investigations in 5 cases and detected incomplete/wrong diagnoses in 7 cases. Conclusions: The results of the present meta-analysis support the use of preoperative CT scans for nonsyndromic craniosynostosis in the absence of alternative imaging modalities. The results also suggest that in properly selected patients, alternative imaging modalities may be appropriate, potentially obviating the need for CT scans.